Application of frequency-locking cavity-enhanced spectroscopy for highly sensitive gas sensing: a review. Issue 5 (28th May 2022) - Hu, Jin; Wan, Fu; Wang, Pinyi; Ge, Hu; Chen, Weigen
Abstract: Spectroscopic gas sensing technologies based on absorption and Raman scattering are fast, nondestructive, long-term stable and highly selective. By making use of an optically resonant cavity, the sensitivity can be enhanced hundreds to thousands of times. However, frequency-locking technology is necessary to maintain a stable resonant condition. In this review, various applications of Pound-Drever-Hall (PDH) and optical feedback (OF) frequency-locking cavity-enhanced spectroscopy (cavity ring-down spectroscopy, cavity-enhanced absorption spectroscopy and cavity-enhanced Raman spectroscopy) for highly sensitive gas sensing are presented. The effect of frequency-locking cavity-enhanced spectroscopy for improving the sensitivity of gas sensing is demonstrated. In addition, the key parameters and advantages as well as limitations of different frequency-locking cavity-enhanced spectroscopy are summarized and discussed.